MCB Connection Troubleshooting Using Dial Switch - Dharsan, D.; Vijaya, S.; Laxmi, P. Harini; Narmadhai, N. (Journal of Electronics and Informatics, 2022)
The existing Miniature Circuit Breakers (MCB) connections have no indication on where the power is supplied by the MCB as the identification provided in MCB during installation is either damaged or missing which makes the troubleshooting difficult for the user. This project aims to solve the problem by using dial switches to indicate the power source. The MCB number to which the switch is connected is identified from the dial position, thus facilitating the troubleshooting process. The dials are made up of numbers from 0 to 9. There are two dials: an outer dial and an inner dial; therefore, up to 99 MCB connections can be realized using this method.
Keywords: Dial switch; MCB identification